Are Scottish degrees better? - Mark P. Taylor; Robert E. Wright (University of Essex, Institute for Social and Economic Research (ISER), 2005)
In wave 12 of the BHPS, information was collected about the institution attended by respondents with higher education, making it possible to identify those who studied and Scottish and English institutions. In this paper, wage equation are estimated with panel data methods in an attempt to measure differences in the rates of return to Scottish and English degrees. The analysis suggests that the earnings returns to higher education are larger in Scotland than in England. However the return to English degrees appears to be higher than for Scottish degrees in both the English and Scottish labour markets.
Keywords: 330